(untitled) (Pulse, 2014)
Background: Bangladesh is an iodine deficient region and the government of Bangladesh, with assistance of UNICEF had initiated a universal salt iodinization program to provide iodized salt by the middle of 1994. Breast milk is the only source of iodine for exclusively breast-fed infants. Iodine deficiency and iodine excess both have bad impact on infants health. Objectives: To assess the iodine status of lactating mothers and their breast-fed infants and to evaluate whether maternal iodine status reflects the iodine status of their breast-fed infants. Material and methods: This observational analytical study was carried out in the department of biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka with active cooperation of Kumudini Womens Medical College Hospital, Mirzapur, Tangail involving fifty lactating mothers and their exclusively breast-fed infants. Early morning urine and breast milk samples were collected in dry and clean plastic containers free from any chemical contamination. Urinary iodine was used as an indicator for assessing iodine status. All statistical analysis was done by using SPSS (Statistical Program for Social Science) 12 version software package for windows. Results: The median (range) urinary iodine concentration of lactating mothers and their breast-fed infants were 225.25 ?g/L (61.50-530.00) and 225.75?g/L (100.50-526.00). 96% (48) mothers had no biochemical iodine deficiency (UIE ?100?g/L), only 4% (2) mothers had mild biochemical iodine deficiency (UIE, 50-99?g/L). There was no biochemical iodine deficiency of breast-fed infants. The median breast-milk iodine concentration was 157?g/L which was more than three times of recommended minimum concentration (50?g/L). Iodine in breast milk of lactating mothers was positively correlated with their urinary iodine excretion (P<0.01). Infants urinary iodine was positively correlated with iodine concentration in breast milk (P<0.01) and also positively correlated with urinary iodine of lactating mothers (P < 0.01). Conclusion: Lactating mothers and their breast-fed infants in this study were iodine sufficient. Iodine status of exclusively breast-fed infants can be determined by the iodine status of their mothers. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20283 Pulse Vol.6 January-December 2013 p.6-11